Current trends and risks associated with the use of therapies based on genome editing - O. A. Rachinskaya; E. V. Melnikova; V. A. Merkulov (Биопрепараты: Профилактика, диагностика, лечение, 2023)
Scientific relevance. To date, multiple approaches to genome editing have been developed based on different genome-editing systems (GESs) and genome modifications that result in single- or double-strand DNA breaks, either in vivo or ex vivo, followed by homologous recombination or non-homologous end joining to restore the sequence. However, the use of GESs is associated with a number of potential risks arising from the complex biology of such medicinal products and the fundamental role of their target, i.e. the DNA molecule.Aim. This study analysed the most relevant trends and risks associated with medicinal products based on genome editing, the ways taken to overcome these risks, and the research methods used to identify and control the development of undesirable effects.According to the literature, the adverse effects of GESs may arise both from the methods used to deliver GES components into the cell and from the functional activity of the GES itself, which includes insufficient on-target or undesirable off-target effects. This review indicates the main risks associated with the use of GESs. Preferable strategies to mitigate the risks of using GESs include repairing DNA breaks by homologous recombination, selecting GESs and related endonucleases that have greater specificity and restriction accuracy, increasing guide RNA specificity (for CRISPR/Cas), correcting the activity of the system regulating the cell cycle and apoptosis in a controlled manner, regulating the duration of expression and persistence of GES components in cells, etc.Conclusions. The requirement to include quality, efficacy, and safety data when submitting registration dossiers for advanced therapy medicinal products prompts the discussion of the main risks associated with such products.